Mental rotation of tactical instruction displays affects information processing demand and execution accuracy in basketball - Koopmann, T.; Steggemann-Weinrich, Y.; Baumeister, J.; Krause, D. (Research Quarterly for Exercise and Sport, 2017)
Purpose: In sports games, coaches often use tactic boards to present tactical instructions during time-outs (e.g., 20 s to 60 s in basketball). Instructions should be presented in a way that enables fast and errorless information processing for the players. The aim of this study was to test the effect of different orientations of visual tactical displays on observation time and execution performance. High affordances in visual-spatial transformation (e.g., mental rotation processes) might impede information processing and might decrease execution performance with regard to the instructed playing patterns. Method: In a within-subjects design with 1 factor, 10 novice students were instructed with visual tactical instructions of basketball playing patterns with different orientations either showing the playing pattern with low spatial disparity to the players` on-court perspective (basket on top) or upside down (basket on bottom). Results: The self-chosen time for watching the pattern before execution was significantly shorter and spatial accuracy in pattern execution was significantly higher when the instructional perspective and the real perspective on the basketball court had a congruent orientation. Conclusion: The effects might be explained by interfering mental rotation processes that are necessary to transform the instructional perspective into the players` actual perspective while standing on the court or imagining themselves standing on the court. According to these results, coaches should align their tactic boards to their players` on-court viewing perspective.